Heavier birth weight associated with taller height but not age at menarche in US women born 1991‐1998. Issue 5 (26th March 2017) - Workman, Megan; Kelly, Karina
Abstract: Objectives: Heavier birth weight predicts taller adult height, but it remains unknown the extent to which this additional height increment results from a faster average growth rate versus an extension of the growth period. Aiming to distinguish these effects, this study examined associations between birth weight (BW), age at menarche (an established proxy for growth duration), and near‐adult height in a cohort of US young women born in the 1990s. Methods: Multiple regression evaluated age‐adjusted height as an outcome of BW, age at menarche, indicators of family socioeconomic status, and other potential confounders in a sample of US teens who participated in the National Health and Nutrition Examination Survey between 2007 and 2012 ( N  =   342). Relevant interactions were also evaluated. Results: Mean ± SD was 11.9 ± 1.2 years and 3262 ± 592 g for age at menarche and BW, respectively. BW did not predict age at menarche ( β  = –.01, p  = .838). Girls were 1.3 cm taller per year delay in menarche ( p  < .001) and 2.9 cm taller per 1 kg increase in BW ( p  < .001). Additionally, the greatest gain in height associated with delayed menarche was observed among the heaviest BW quartile. Conclusions: Girls born heavier were taller but experienced menarche at similar ages to girls born lighter. To the extent that age at menarche reflected growth duration, these results demonstrate faster average growth among heavier‐born girls. Consistent with fetal programming of average growth rate, these results held after adjustment for confounders of postnatal growth like family socioeconomic status.